Illegals abortions and utero-digestives lesions: retrospective study of 12 cases in the Department of Gynecology and Obstetrics at the Treichville teaching hospital (Abidjan, Cote D’ivoire) - Yao, Ignace N.; Menin, Michelle M.; N’Dri, Konan J.; Traore, Lassina; Oyelade, Mouhideen A.; Saki, Corneille T.; Okon, Gérard; Guie, Privat Y.; Anongba, Simplice D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Traumatic intestinal digestive damage after abortion by endo-uterine manoeuvres are not uncommon. The purpose of this study is to describe the diagnostic, therapeutic and prognostic aspects of these lesions. Methods: This is a retrospective study of 3 years on patients with a uterine lesion associated with a digestive traumatic injury during illegal abortions endo-uterine manoeuvres. Results: 12 patients with a median age of 23, 9 are included. The clinical manifestations are not specific: impairment of the general condition 33.3%; hyperthermia 83.3% (or 10 cases); digestive disorders such as diarrhoea 25%, vomiting 33.3%; abdominal pain 100%; occlusive syndrome 16.7%; acute abdominal syndrome 75%. The seat of traumatic injuries is variable. The lesions were for hail alone in 4 cases (33.3%), colon alone for 2 cases (16.7%), rectum 1 case and epiploon 2 cases. In these 3 cases, the lesions were associated, sitting on both the hail and the colon at a time. All these lesions were associated with uterine perforation of variable siege. The therapeutic management consisted of a small bowel resection with ileostomy in 5 cases or 41.7%; colon resection with colostomy 3 cases or 25%; suture lesions after beveling beiges 5 cases either 41, 7 in 2 cases, we performed haemostasis on the bleeding epiploon. Treatment of the uterine lesion was conservative 75% of the time. The evolution on the 10 patients was favorable, 83.3%. Two patients died early in the operative course after septic shock. Conclusions: The digestive lesions are a factor aggravating the prognosis of post-abortion uterine manoeuvres. Their management must be rapid and requires close collaboration between the digestive surgeon and the Gynecologist.